2019
DOI: 10.12659/msm.918416
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA Nuclear Enriched Abundant Transcript 1 (NEAT1) Regulates Proliferation, Apoptosis, and Inflammation of Chondrocytes via the miR-181a/Glycerol-3-Phosphate Dehydrogenase 1-Like (GPD1L) Axis

Abstract: Departmental sources Background: Osteoarthritis (OA) is one of the most common chronic musculoskeletal diseases, yet to date it lacks effective therapeutic strategies. Increasing evidence suggests that long noncoding RNAs (lncRNAs) serve pivotal roles in the occurrence and development of OA. However, the possible molecular mechanism involving lncRNAs, such as nuclear enriched abundant transcript 1 (NEAT1), in OA progression is still unclear. Material/Methods: First, NEAT1 and miR-181a expression in OA synovium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…Additionally, the in vivo experiments suggested that downregulation of lncRNA NEAT1 shuttled by PBMC-derived exos impeded RA deterioration of mice. It has been demonstrated that lncRNA NEAT1 restricted cell growth, enhanced the apoptotic rate and the in?ammatory cytokines released in OA chondrocytes (Wang et al, 2019). Similar to our results, lncRNA NEAT1 expression was found to be upregulated in OA tissues, and the concentrations of inflammatory factors were declined, cell viability of synoviocyte was inhibited by lncRNA NEAT1 knockdown (Wang et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, the in vivo experiments suggested that downregulation of lncRNA NEAT1 shuttled by PBMC-derived exos impeded RA deterioration of mice. It has been demonstrated that lncRNA NEAT1 restricted cell growth, enhanced the apoptotic rate and the in?ammatory cytokines released in OA chondrocytes (Wang et al, 2019). Similar to our results, lncRNA NEAT1 expression was found to be upregulated in OA tissues, and the concentrations of inflammatory factors were declined, cell viability of synoviocyte was inhibited by lncRNA NEAT1 knockdown (Wang et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…But overexpression of NEAT1 promoted cell proliferation and suppressed apoptosis in ovarian cancer cells 13 . Researchers also found that downregulation of NEAT1 aggravated progression of osteoarthritis via modulating the miR-181a/GPD1 L axis 14 . As our results showed, NEAT1 was downregulated in NB tissues and cell lines, while upregulation of NEAT1 inhibited the cell proliferation, migration, and invasion in NB cells.…”
Section: Discussionmentioning
confidence: 98%
“…Xu et al proposed that NEAT1 could mitigate the acuteon-chronic liver failure by blocking the TRAF6-meidated inflammatory response [31], and Zhang et al claimed that the oxidative stress-induced vascular endothelial cell injury was suppressed by NEAT1 through the activation of the miR-181d-5p/CDKN3 axis [32]. And NEAT1 impeded the progression of osteoarthritis via the regulation of miR-181a-GPD1L axis [33]. Additionally, Zeng et al attested that NEAT1 exacerbated cell apoptosis in chronic myeloid leukemia (CML) [34].…”
Section: Discussionmentioning
confidence: 99%